ENVIRONMENTAL ENGINEERING SCIENCE, CHEMICAL ENGINEERING AND A VISIONARY FUTURE - A FAR-REACHING – REVIEW. - SUKANCHAN PALIT, (International Journal of Pharma and Bio Sciences, 2015)
The science and technology of environmental engineering and chemical engineering is moving forward by leaps and bounds. Scientific vision, scientific understanding and the immense challenges are the hallmarks of newer scientific endeavour. History of science and technology and history of scientific progress is witnessing newer future direction and innovative directions. In today’s world of cut-throat competition and scientific urge to excel, challenges and future trends needs to be reshaped. History of human civilization is ushering in a new beginning. Global warming, global water shortage and industrial pollution has propelled scientific endeavour to move towards visionary direction. Scientific tools and environmental engineering techniques has re-envisioned the entire scenario of industrial pollution control and application of chemical engineering. History of science is veritably ushering in a new era. The author gleans and gives deep insight to the recent trends of chemical engineering and application of environmental engineering techniques to tackle global industrial pollution, global water shortage and the future of energy and environmental sustainability. The success of this treatise is the invaluable research pursuit in the field of environmental engineering science and its wide world of water treatment techniques. Energy and environmental sustainability is slowly and steadfastly moving towards a new realm of scientific vision and scientific fortitude. Chemical engineering and environmental engineering science in today’s world have an unsevered umbilical cord. Challenge, vision and urge to excel will lead a long way in opening new doors of innovation in decades and years to come.